Advancing sustainability in healthcare facilities: A systematic review of strategies for energy efficiency, stakeholder engagement, and environmental impact - Mohd Soleh, Anis Syahmina; Putri Zulaiha, Razi; Nurhidayah, Azmy; Noram Irwan, Ramli; Fatin Zafirah, Mansur; Roziah, Zailan (RSIS International, 2025)
The growing global population and aging demographics have created extraordinary pressure on healthcare systems, necessitating an immediate adoption of sustainable practices within healthcare facilities. In response to these challenges, many healthcare organizations are implementing energy-efficient systems and renewable energy sources, such as solar panels and utilizing energy-efficient lighting and HVAC systems to reduce greenhouse gas emissions and operational costs. However, despite the increasing awareness of healthcare facilities environmental impact, research on the integration of environmentally sustainable approaches throughout the healthcare delivery process, encompassing construction, design, and daily operations, while simultaneously addressing environmental, social and economic sustainability remains inadequate. Hence, this study utilized systematic literature review to investigate the effective strategies that can be implemented across the entire healthcare operations. The review was conducted based on ROSES (Reporting standards for Systematic Evidence Syntheses) framework. This review identified five (5) main themes along with thirteen (13) sub-themes that cover strategies for advancing sustainability in healthcare facilities at different levels. The findings underscore the importance of operational efficiency at every stage of healthcare delivery while maintaining high-quality patient care. Additionally, the results emphasize the necessity of involving multiple stakeholders throughout the decision-making process and calls for further research to address existing gaps in the literature regarding sustainability in healthcare. This study also contributes in achieving Sustainable Development Goals (SDG’s) SDG 3 (Good Health and Well -Being), SDG 9 (Industry, Innovation and Infrastructure), and SDG13 (Climate Action).